A cross-sectional study on under-emphasized sex determining parameters of femur - Siddapur, Kishan R.; Siddapur, Geetha Kishan (International Journal of Research in Medical Sciences, 2017)
Background: There have been researches done based on using ‘Maximum length’ of femur for sex determination. We, the authors of the present study, formulated an index including both (maximum length & girth) and named it as Femoral Girth Index (FGI). An attempt has been made by the authors, with this study, to arrive at appropriate conclusions regarding sex determination using dry femurs representing South-Eastern India (Kancheepuram district region) using three parameters namely, ‘Maximum length’, ‘Maximum girth’ and FGI. Methods: FGI was calculated using the observed values of ‘Maximum length’ and ‘Maximum girth’ of the femurs. Formula used for calculating the FGI was, “Maximum girth of shaft of femur/Maximum length of femur x 100”. Statistical analysis was done using three parameters, namely, maximal length of femur (L), maximum girth of femur (G) and FGI. Significance of the results was assessed implementing unpaired t test. Results: The results were very significant with the application of unpaired t test in relation to the three parameters, maximal length of femur, maximum girth of femur and femoral girth index. Conclusions: We believe that the study results can be reliably used for dry, fully ossified femurs of southern India. FGI, when more than 19.57, is indicative of males and when less than 19.57, is indicative of females.